Pengaruh model pembelajaran problem based learning terhadap hasil belajar siswa kelas X pada materi struktur atom di SMA katolik santa rosa de lima tondano - Chrisly Durant; Emma Juline Pongoh; Sonny Lumingkewas (Chemistry Department, Universitas Negeri Manado, 2019)
Problem Based Learning model is a problem-based learning model that exposes students to practical problems to be solved that focus on the final results. The purpose of this study is to find out whether the Problem Based Learning learning model on atomic structure material is better than conventional learning models. The population in this study were all class X students of Santa Rosa de Lima Tondano Catholic High School. The sample of this study was class XA and class XB Catholic School Santa Rosa de Lima Tondano with the number of students 30 people, for the experimental class 15 people and the control class 15 people, in the even semester the academic year 2018/2019.Hypothesis testing uses the t-test to see differences in student learning outcomes between the experimental class and the control class. Based on the results of the study obtained the value of t_count (4.21)> t_table (1.701) at the real level α = 0.05. So that H_0 is rejected and H_1 is accepted. where the average value obtained in the experimental class 82.66 and the average value for the control class 71.33. So the conclusion is that there is a positive effect of the implementation of the Problem Based Learning learning model on atomic structure material on student learning outcomes at Santa Rosa de Lima Tondano Catholic High School.